2011
DOI: 10.4081/reumatismo.2009.125
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of methotrexate in psoriatic arthritis

Abstract: Objective. The purpose of this study was to evaluate the long-term survival rate of Methotrexate (MTX) in the peripheral joint involvement of psoriatic arthritis (PsA) in a setting of everyday clinical practice. Methods. This was an observational restrospective study performed using the data from a dermatological-rheumatological PsA clinic. All of the patients evaluated at this clinic from March 1997 to December 2007 who were started on MTX alone, had a three-year follow-up time or had discontinued the therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
1
7
1
3
Order By: Relevance
“…Conversely, Dalkilic et al described a lower GI intolerance to MTX, corresponding to 28.6% [17]. The Italian cohort only reported 10% of adverse events and patients had a good tolerance to MTX [15]. Comparisons between these cohort is difficult due, among other reasons, to loss of follow up, the variable number of patients and the median MTX dose used included in each study.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, Dalkilic et al described a lower GI intolerance to MTX, corresponding to 28.6% [17]. The Italian cohort only reported 10% of adverse events and patients had a good tolerance to MTX [15]. Comparisons between these cohort is difficult due, among other reasons, to loss of follow up, the variable number of patients and the median MTX dose used included in each study.…”
Section: Discussionmentioning
confidence: 97%
“…Дозу препарата увеличивали постепенно, каждые 4 нед, с 7,5 до 25 мг/нед к 5-му месяцу терапии, применение глюкокортикоидов (ГК) внутрь не допускалось, кроме однократного внутрисуставного введения ГК в течение всего срока наблюдения. Авторы делают вывод о недостаточной эффективности МТ в таблетках в низкой дозе 15 мг/нед [45]. Несмотря на небольшой объем данных, исследователи предполагают, что еженедельная доза >15 мг является своего рода пороговой, на фоне которой вероятность проявления клинического эффекта МТ повышается.…”
Section: результаты клинических исследований эффективности метотрексаunclassified
“…Ricci et al (37) in their observational retrospective analysis demonstrated that in a setting of clinical practice MTX had good performance over 3 years in patients with peripheral PsA. Almost 60% of them were still taking this drug at the end of the study period, and toxicity was more than acceptable.…”
Section: Mtxmentioning
confidence: 99%